A PERSPECTIVE TOWARDS VACCINATION AGAINST ATHEROSCLEROSIS - Mohiuddin, Mohd Nasir; Afreen, Sana; Khan, M.Kaleemullah; Khan, Nusaibah Ahmed; Adil, Mir S; Chacham, Swati (Medico Research Chronicles, 2015)
Atherosclerosis is a disease of the blood vessels characterized by plaque buildup in the arteries. Immunization is the process by which an individual's immune system becomes fortified against an agent. Atherosclerosis is similar to inflammatory/ autoimmune diseases like rheumatoid arthritis and multiple sclerosis. Data from the previous studies suggest that these diseases may be treated by vaccination. It has been reported that by using monoclonal antibodies against specific antigens, passive immunization confers athero-protective effects. Atherosclerotic lesion formation in LDL receptor (-/-) (LDLR (-/-)) mice was significantly reduced by monoclonal IgG preparations reactive to cardiolipin or LDL. It was recently shown that atherosclerosis in animal models was reduced by a recombinant human IgG antibody against an MDA-modified about-100 derived peptide antigen. It is believed that oxidized LDL which causes intimal inflammation and foam cell formation has a key role in atherosclerosis. Neoepitopes are the antigenic sequences that are normally absent or concealed but which become available after the oxidation of LDL. Observations from several studies have shown that immunization changes favorably the composition of established plaques, indicated by decreased plaque inflammation and increased collagen content. Immunization against many infectious diseases completely prevents the development of the disease; however, it will not completely prevent the development of atherosclerosis. The studies performed so far have suggested that immunization may reduce the development of atherosclerosis by 50-60%. However, many questions need to be answered such as vaccine stability, safety, the durability of effects, efficacy endpoints, etc.